Notes on the lichen genus Rhizoplaca from continental Antarctica and on some other species from northern Victoria Land. - CASTELLO, Miris (The Lichenologist, 2010)
Five taxa of the genera Omphalodina and Rhizoplaca known from continental Antarctica are reassessed in order to identify a remarkable species collected from northern Victoria Land, for which the new combination Rhizoplaca macleanii (C.W. Dodge) Castello is proposed here. This poorly known species is known only from continental Antarctica. Two synonyms are discussed: Omphalodina exsulans (Th. Fr.) C. W. Dodge and O. siplei (C.W. Dodge &G. E. Baker) C. W. Dodge are synonyms of Rhizoplaca melanophthalma (DC.) Leuckert & Poelt. The correct name of another species is Tephromela priestleyi (C. W. Dodge) Øvstedal. The name O. johnstonii (C. W. Dodge) C. W. Dodge should be abandoned, type material being too scanty for a reliable identification. A contribution to the flora of the Terra Nova Bay area (northern Victoria Land) is provided, with two additional species, including Buellia vilis Th. Fr. new to Antarctic regions, and two nomenclatural corrections.